Rencana Implementasi Kebijakan Promosi Kesehatan di Rumah Sakit Universitas Airlangga - Bintang Gumilang; Ratna Dwi Wulandari (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2016)
Hospital is a health institution that provide comprehensive health service which is including aspects of promote, preventive, curative, and also rehabilitative. To achieve the goal, the government has been releasedRegulation of the Minister of Health Number 4 Year 2012 about Technical Instructions of Health Promotion in Hospital. In means by all hospitals must implement health promotion in their institution. Based on the earliersurvey, the implementation of the regulation of Health Promotion Hospital (PKRS) in the Universitas Airlangga Hospital was considered less than optimal. The purpose of this research was to analyze the planning factor ofHPH policy implementation. The number of respondents are seven which chosen by purposive sampling. This research was conducted by deep interview and observation method. The results showed that the planning ofPKRS unit has not been prepared as it should be as set out in the regulations. There is neither strategic planning nor operational planning. Unit PKRS not yet have a systematic and structured organization. Qualification ofhuman resources in general are already qualified, but need additional quantity. PKRS unit does not have special health worker health promotion.Keywords: health promotion hospital, implementation, planning, policy